Exploring the effect of sampling, protogyny, and larval advection on stock estimates subject to no-take closures in a spatially complex coral reef line fishery on the Great Barrier Reef, Australia1 - Little, L. Richard; Punt, André E; Tuck, Geoffrey N; Mapstone, Bruce D (Canadian journal of fisheries and aquatic sciences, 2017)
Simulation is used to evaluate the ability of a two-region, age-structured assessment model to provide accurate and precise estimates of stock status (i.e., the ratio of female spawning biomass to unfished female spawning biomass) for coral trout (Plectropomus leopardus) on the Great Barrier Reef (GBR), Australia. The model used to generate the simulated data used by the assessment model is a spatially complex age- and sex-structured population dynamics model that captures the protogynous nature of coral trout. Stock status is underestimated (negatively biased), with the extent of negative bias related to mis-specification of the breeding strategy of the target fish stock, the impact of the amount of larval connectivity among reefs, the number of reefs closed to fishing, as well as exploitation rates. The estimates of stock status were less negatively biased when fishery-independent index and age- and length-composition data were available from closed areas. The results will inform the development of management strategies for coral trout in the GBR and highlight the importance of basing evaluations of estimation and management performance on operating models that capture ecologically important processes such as metapopulation dynamics and protogynous life history.